2013
DOI: 10.1080/10454446.2012.732548
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Habit, Childhood Consumption, Familiarity, and Attitudes Across Seafood Consumption Segments in Australia

Abstract: Australian consumers hold very favourable attitudes toward seafood with key drivers to consumption being taste, convenience, diet variety and health benefits. Nevertheless, despite these positive attitudes, seafood consumption remains below many other countries. In this paper, we investigate the influence of habit including regular childhood consumption, familiarity with seafood, and attitudes toward seafood on seafood consumption and consumption occasions. Habit and lack of familiarity with seafood were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
(17 reference statements)
2
35
0
Order By: Relevance
“…Similar results were also observed in Norway where high fish consumption (three or more times per week) in 45-69 year old women was correlated to high fish consumption during their childhood (Trondsen et al, 2003(Trondsen et al, , 2004a(Trondsen et al, , 2004b. The role of childhood habits having a positive effect on seafood consumption in adulthood was also confirmed by Birch and Lawley (2014) who found that consuming fish regularly as a child is associated to a more favourable attitude towards fish and a greater familiarity with this product. However, these authors did not find any significant evidence that regular fish consumption during childhood translates into the same behaviour in adulthood.…”
Section: Fish Eating Habitssupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were also observed in Norway where high fish consumption (three or more times per week) in 45-69 year old women was correlated to high fish consumption during their childhood (Trondsen et al, 2003(Trondsen et al, , 2004a(Trondsen et al, , 2004b. The role of childhood habits having a positive effect on seafood consumption in adulthood was also confirmed by Birch and Lawley (2014) who found that consuming fish regularly as a child is associated to a more favourable attitude towards fish and a greater familiarity with this product. However, these authors did not find any significant evidence that regular fish consumption during childhood translates into the same behaviour in adulthood.…”
Section: Fish Eating Habitssupporting
confidence: 84%
“…more healthy fish consumption. Thus policy makers and marketers should reflect more on how to employ principles of behavioural economics to trigger behavioural changes which might be stimulated by visual cues, in-store fish tastings, cooking demonstrations, or special price promotions to encourage trial at the point of sale (Birch & Lawley, 2014;van't Riet, Sijtsema, Hans, & De Bruijnb, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also shown in Table 2, the frequency of consumption of crustacean product found Palermo dominating ‘twice per month’ before Naples and Rome dominating ‘at least once a month’, and Turin dominating ‘never’ before Milan. Previously reported cross-cultural and single cross-sectional studies have underlined that knowledge, skills, and self-confidence in the selection and preparation of fishery products can positively/significantly impact on its consumption frequency (10, 27, 30, 31). …”
Section: Resultsmentioning
confidence: 99%
“…Studies of fish consumption reveal that many consumers are not confident with fish and experience difficulty in evaluating, selecting, storing, and preparing fish (Birch & Lawley, ; Juhl & Poulsen, ; McManus et al, ; Sogn‐Grundvåg & Østli, ; Sveinsdóttir et al, ). This lack of confidence contributes to lower levels of fish consumption.…”
Section: Theoretical Frameworkmentioning
confidence: 99%